Cutting Rice Methane Emissions: Scalable Strategies for Business Action and Accountability - World Business Council for Sustainable Development (World Business Council for Sustainable Development, 2025)
This guidance document, "Cutting Rice Methane Emissions: Scalable Strategies for Business Action and Accountability," provides a framework for companies in the agri-food value chain to take credible, measurable action to reduce methane emissions from rice cultivation, a source that accounts for approximately 12% of global methane releases. It helps companies navigate the complex reporting landscape by aligning global frameworks like the GHG Protocol and SBTI FLAG with rice-specific standards (e.g., Verra, Gold Standard). The core focus is on identifying and deploying effective Measurement, Reporting, and Verification (MRV) approaches, which includes combining methods such as farmer engagement, remote sensing, and biogeochemical models to accurately measure and track impact. The report operationalizes these efforts through a three-step 'Rice Action Plan' (Disclose, Plan, Track) and outlines six categories of mitigation solutions, including improved water management practices like Alternate Wetting and Drying (AWD), to drive the transition to low-emission, resilient rice production systems.